BIOGEOGRAPHY AND PATTERN VARIATION OF KINGSNAKES, LAMPROPELTIS GETULA, IN THE APALACHICOLA REGION OF FLORIDA - Means, D. Bruce; Krysko, Kenneth L. (Contemporary Herpetology, 2001)
Morphology of kingsnakes, Lampropeltis getula, is described and analyzed in the Apalachicola region of the Florida panhandle. Populations inhabiting the eastern Apalachicola Lowlands, a distinct biotic province, are different from the surrounding populations in having fewer and wider light body crossbands, distinct ontogenetic interband lightening, unique ventral patterns, and the presence of non-banded (striped and patternless) individuals. We conclude that the name L. g. goini as well as the hypothesis that Apalachicola L. getula are relict populations of intergrades between L. g. getula and L. g. floridana are invalid. We believe the polymorphic eastern Apalachicola Lowlands populations are most closely related to L. g. getula, and evolved in isolation on a barrier island or the coastal strand of a peninsula during one of the many higher stands of sea in the Pleistocene.